Peran Radiologi dalam Menegakkan Diagnosis Ileus pada Pasien CKD dengan Nyeri Abdomen, Konstipasi, dan Anemia Penyakit Kronik: Laporan Kasus - Divia Denisa Sitinjak; Ricky Ramadhan (CV. Jasa Sukses Abadi, 2026)
Ileus often presents as mechanical bowel obstruction, thereby posing a significant diagnostic challenge in patients with advanced chronic kidney disease (CKD). This is because the symptoms of uraemia overlap with those of acute abdominal conditions. The use of contrast-enhanced computed tomography (CT) is generally avoided due to the risk of nephropathy, making non-contrast multimodal imaging crucial. This case report analyses the role of integrating plain abdominal radiographs and ultrasound (US) in distinguishing between obstructive and paralytic ileus. A 72-year-old male patient with stage 5 CKD presented with acute abdominal pain, persistent vomiting, distension and total constipation. Assessment confirmed normocytic normochromic anaemia, severe uraemia, hyponatraemia and hyperkalaemia. A plain abdominal X-ray showed dilated small bowel with a herringbone pattern and the absence of rectal gas, which was initially interpreted as high-site mechanical obstruction. However, dynamic abdominal ultrasound revealed markedly hypoperistaltic dilated bowel loops with wall thickening, leading to a diagnosis of secondary paralytic ileus due to uraemic enteropathy. The patient refused dialysis and surgical intervention but showed partial improvement through conservative management comprising decompression, prokinetic therapy and electrolyte correction. This case underscores that a combination of static and dynamic non-contrast imaging is essential in reconciling conventional pseudo-mechanical findings with functional dysmotility. Furthermore, the comorbidity of anaemia in PGK reduces physiological tolerance to intestinal ischaemia and requires a higher level of clinical vigilance.